Perancangan Sistem Perencanaan dan Penjadwalan Produksi di PT. Bondi Syad Mulia - Renny Olivia Sia; I Gede Agus Widyadana (Jurnal Titra, 2013)
This research is a case study conducted at PT. Bondi Syad Mulia, which is a galvanishing services company. Production planning at PT. Bondi Syad Mulia combined with production department, so that the work does not focus and cause some problems in production planning. The proposed planning system is set up the PPIC department, so that production planning does not interfere with affairs that must be done by the production department. Another issue that arises is the production delays because there is do not have a good system of production scheduling. Determine the right scheduling for a company is very important, but not easy, especially for a service company that manufactures a wide range of products. This thesis aims to get the system scheduling to minimize makespan, thus increasing the amount of output produced. The method used to achieve these criteria is Algorithm Campbell, Dudek, and Smith (CDS) and Shortest Processing Time method (SPT). CDS scheduling algorithm results provide several alternative job sequences that generate makespan value is almost the same, but there is a job sequence that produces the smallest makespan value compared to other alternative job sequences.